2013
DOI: 10.1371/journal.pone.0057240
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Creatinine- and/or Cystatin C-Based Equations for Estimation of Glomerular Filtration Rates in Chinese Patients with Chronic Kidney Disease

Abstract: Objective To establish equations for the estimation of glomerular filtration rates (eGFRs) based on serum creatinine (SCr) and/or serum cystatin C (SCysC) in Chinese patients with chronic kidney disease (CKD), and to compare the new equations with both the reference GFR (rGFR) and the literature equations to evaluate their applicability.Methods The 788 Chinese CKD patients were randomly divided into two groups, the training group and the testing group, to establish new eGFR-formulas based on serum CysC and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…2 The combined equation is commonly employed in adult hospitals as the method for eGFR in adults, replacing the popular MDRD eGFR. 24,25 Similarly to others in adults and children, we found that all three combined (Scr with Scys) equations outperformed equations that used the Scr or Scys, alone.…”
Section: Discussionsupporting
confidence: 83%
“…2 The combined equation is commonly employed in adult hospitals as the method for eGFR in adults, replacing the popular MDRD eGFR. 24,25 Similarly to others in adults and children, we found that all three combined (Scr with Scys) equations outperformed equations that used the Scr or Scys, alone.…”
Section: Discussionsupporting
confidence: 83%
“…Chinese investigators have proposed a series of GFR estimation equations based on serum creatinine or/and cystatin C in recent years . Yet, only limited data exist outside the development cohort regarding their application in Chinese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…22 Chinese investigators have proposed a series of GFR estimation equations based on serum creatinine or/and cystatin C in recent years. [4][5][6][7] Yet, only limited data exist outside the development cohort regarding their application in Chinese individuals. In our previous study, CKD-EPIscr-cys achieved ideal performance in overall population while Mascr and Mascr-cys equations appeared more biased and less accurate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold standard procedures for measurement of GFR (inulin, iohexol, 51Cr-EDTA, 99mTc-DTPA and 125I-iothalamate clearance) are timeconsuming, have side effects for patient or expensive. 11,12 Estimated GFR (eGFR) formulas have been developed and used in more than 80% of clinical laboratories in the United States because of the aforementioned problems. 13 The most common formulas used in the calculation of eGFR include MDRD and recently CKD-EPI equations.…”
Section: Biochemistry Analysismentioning
confidence: 99%